Peningkatan Hasil Belajar Pendidikan Agama Kristen Siswa SMP Melalui Metode Outdoor Study - Raulina Panjaitan (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to increase students' interest in PAK class VII at SMPN 3 Tualang using the outdoor study method. This type of research is Classroom Action Research (CAR). This Classroom Action Research was conducted at SMPN 3 Tualang, Tualang District, Siak Regency, for the 2022 academic year. In this study, the authors used the Jigsaw model with the aim of improving or increasing student learning outcomes. Effectiveness of learning Christian Religious Education through the out door study method can increase the learning interest of class VII students of SMPN 3 Tualang so that student learning outcomes increase in the 2022 school year. completed with an average of 70 and not completely completed. Improvements were made in cycle II. In this cycle there was a high increase, out of 15 students only 1 student did not reach the KKM: 75. with an average acquisition of 81.